Improving Marketing Strategies Based on Local Consumer Demand Segmentation for Knitting Products - Topildiev S.R.; Odilova D.B. (International Journal Of Management And Economics Fundamental, 2025)
In this article, segments of the local consumer market for sewing and knitting products in our country, stages of segmentation, improvement of marketing strategies, strategies for segmenting the markets of sewing and knitting products It is proposed to implement ways to improve the segment's share in international markets, demographic segmentation, the promotion of the textile and cottage trade, and the modern system that meets modern requirements.